Stellenwert der Herz-CT in der Diagnostik der koronaren Herzerkrankung: Update 2017 = Value of cardiac CT in the diagnostic work-up of coronary artery disease - Meyer, Mathias; Henzler, Thomas (Der Radiologe, 2017)
The quantification of coronary calcifications using noncontrast-enhanced computed tomography (CT) as well as coronary CT angiography (cCTA) have rapidly evolved in the recent years. Nowadays, both techniques are increasingly clinically accepted regarding risk stratification and accurate exclusion of significant coronary artery disease (CAD). The higher acceptance of cCTA is mainly based on the higher robustness, lower radiation exposure through continuous technical innovations as well as by the growing scientific evidence. The poor predictive value of cCTA for predicting the hemodynamic significance of detected coronary artery stenosis may be improved by continuous technical developments in the area of functional imaging. The aim of this educational article is to summarize the current clinical status of calcium scoring and morphological cCTA and to provide an overview on novel functional CT techniques.
Gesehen am 04.06.2018